Creating Hyphenation on a Journal Article - Ivanov, Akasma (CV TOPAZART, 2023)
In writing, we use a lot of compound words. Compound words include nouns like president-elect and sister-in-law, verbs like back-paddle and flash-freeze, and adjectives like best-case and top-of-the-line. Using a hyphen to connect multiple words, these words rely on the same punctuation. But not every journal management does it. The paper contains word space and could be more interesting to be performed. This study examines how to make a hyphenation of the journal article, comparing using Microsoft Word and Adobe InDesign. This study uses a practical case of a paper composed using Microsoft Word and Adobe InDesign. The results show that either Microsoft Word or Adobe InDesign can perform the article better visually because there is no white space in the papers.er visually because of no white space in the documents.